the PEMBERDAYAAN MASYARAKAT DALAM PENCEGAHAN STUNTING MELALUI LOMBA BALITA SEHAT DI KECAMATAN LANDONO - Farming , Farming; Kartini, Kartini; Askrening, Askrening; Fatmawati, Fatmawati; Hikmandayani, Hikmandayani (Jurnal Stunting Pesisir dan Aplikasinya, 2026)
Stunting remains a major public health problem that has long-term impacts on the quality of human resources. One effective strategy for stunting prevention is community empowerment through improving knowledge, attitudes, and family participation in monitoring child growth and development. This community service activity aimed to empower the community in stunting prevention through the implementation of a Healthy Toddler Competition in Landono District. The methods included nutrition and child health education, anthropometric measurements (body weight, height, and nutritional status), as well as assessments of parenting practices and feeding patterns. The targets of this activity were mothers and toddlers living in Landono District. The results showed an improvement in mothers’ knowledge regarding stunting prevention, balanced nutrition, and growth monitoring of toddlers. In addition, the competition increased community motivation to actively monitor children’s health and growth. The Healthy Toddler Competition also served as an effective educational medium to raise collective community awareness of the importance of early stunting prevention. In conclusion, community empowerment through the Healthy Toddler Competition can be an effective promotive and preventive strategy for stunting prevention at the community level.